Financing public schools with private funds: Efficiency–equity trade-off of multi-stakeholder school financing in Punjab, Pakistan - Sakamoto, Jutaro (Education Policy Analysis Archives, 2022)
Governments and development partners encourage public school authorities to mobilize private funds from diverse non-state stakeholders as a means to expand funding sources to provide quality education for all. While financing public schools with private funds is expected to promote the efficient use of resources due to increased accountability, it raises concerns about financial equity. Using public school panel data from Learning and Educational Achievements in Punjab Schools (LEAPS) in Pakistan, this study examines how private funds mobilized from different stakeholders are associated with efficiency in educating students at a given achievement level and equity in school finance. School fixed effects analyses show that schools relying on education fees or local community contributions were more likely to reduce inefficient capital expenditure. In girls’ schools, financial dependency on private donors is also associated with a reduction in capital expenditure. However, the results suggest that a heavy reliance on education fees and private donors makes schools less efficient. I find no evidence that mobilizing private-fund revenue widened financial inequity. The findings demonstrate the importance of understanding the differential effects of private-fund revenue to develop effective multi-stakeholder financing systems that improve student achievement in a cost-effective manner and ensure financial equity.